Formal Specification and Verification of Smart Contracts for Azure Blockchain - Wang, Yuepeng; Lahiri, Shuvendu; Chen, Shuo; Pan, Rong; Dillig, Isil; Born, Cody; Naseer, Immad (2019)
Ensuring correctness of smart contracts is paramount to ensuring trust in blockchain-based systems. This paper studies the safety and security of smart contracts in the Azure Blockchain Workbench, an enterprise Blockchain-as-a-Service offering from Microsoft. As part of this study, we formalize semantic conformance of smart contracts against a state machine model with access-control policy and develop a highly-automated formal verifier for Solidity that can produce proofs as well as counterexamples. We have applied our verifier VeriSol to analyze all contracts shipped with the Azure Blockchain Workbench, which includes application samples as well as a governance contract for Proof of Authority (PoA). We have found previously unknown bugs in these published smart contracts. After fixing these bugs, VeriSol was able to successfully perform full verification for all of these contracts.